Analisis Tata Letak Barang Berdasarkan Frekuensi Perpindahan Barang Menggunakan Analisis ABC - Rahma, Dyah Calystha; Novel, Nurillah Jamil Achmawati (Akademi Sekretari Manajemen Taruna Bakti, 2024)
PT XYZ a prominent logistics aggregator and warehouse company specializing in freight forwarding and warehouse rental services, has established a robust presence with over 300 warehouses spanning 35 cities in Indonesia. Among its esteemed partners is Client X, a company specializing in household appliances, furniture, and electronic goods. Client X relies on PT XYZ's services to efficiently manage its warehouse operations. This research aims to scrutinize the efficacy of Client X's warehouse layout through an ABC analysis. The classification is based on the frequency of goods movement, both inbound (pallet in) and outbound (pallet out), along with the average demand for goods. Data for the analysis is extracted from the past 3 months, employing a simple moving average. Client X's diverse product range falls into three categories: finished goods, assembling, and electronics, each utilizing dedicated storage methods. The inventory comprises 22 SKUs, with 8 falling under fast-moving goods, 6 under medium-moving goods, and 8 categorized as slow-moving. Among the 22 SKUs, item code 1692 emerges as the most dynamic, witnessing a significant movement of 12 pallets in the last 3 months. This research delves into optimizing Client X's warehouse layout, enhancing efficiency, and streamlining operations for sustained success.